Assessing Organizational Efforts to Mobilize Research Knowledge in Education - Levin, Ben; Qi, Jie (Education Policy Analysis Archives, 2013)
This paper presents a framework for evaluating efforts by organizations to share research as exemplified on their websites, then reports the result of an evaluation of these efforts in 100 organizations. The result shows that the overall research sharing efforts of these organizations are modest and not well aligned to evidence on effective practice in this area. Organizations tend to devote more efforts to making products available while interpersonal strategies, though more effective, are less used. Most efforts involve one way communication to potential users. The paper concludes with suggestions for practice and for further research.